METHODS OF TEACHING HISTORY: PROBLEMS AND SOLUTIONS - Yuldoshev Salimjon; Yusupov Shokhbek (Zeta Repository, 2023)
This article is devoted to methods of teaching history, problems and solutions in it. It is said about the experiences of the radical reform of the educational system in our country, raising it to the level of modern requirements, carrying out the work of educating the perfect generation for the future.